radiologic interventions Embolotherapy - Coldwell, Douglas M.; Douglas M. Coldwell (Baltimore, MD : Williams & Wilkins, 1997)
embolotherapy is one of most technically demanding aspects of interventional radiology and allows the interventionalist to act and truly be a real physician .
angiographic cotrol of hemorrhage in trauma -- embolotherapy of tumors -- Embolotherapy of varicoceles.
Embolotherapy. include index ,CD.
Includes bibliographical references and index.
All age.
Keywords: embolotherapy , tumors